AJP Reviewers - Richard H. Price (American Journal of Physics, 2019)
OBJECTIVES: This study aims to compare the effects of dorsal root ganglion pulsed radiofrequency (DRG-PRF) and transforaminal epidural steroid injection (TFESI) on cutaneous silent period (CSP) parameters reflecting spinal inhibition in patients with lumbar radicular pain (LRP). METHODS: In this prospective, single-blind, randomized controlled trial, 36 patients with unilateral LRP due to L4-L5 or L5-S1 disc herniation and chronic pain unresponsive to conservative therapy were randomized to receive DRG-PRF (n=18) or TFESI (n=18). Eighteen healthy volunteers were included as controls. CSP onset latency, offset latency, and duration were recorded at baseline, post-procedure Day 1, Week 1, and Month 1. Pain intensity was assessed using the Numerical Rating Scale (NRS-11), and disability was measured with the Oswestry Disability Index (ODI). RESULTS: At baseline, CSP duration was significantly shorter in both patient groups compared with controls (P=0.024 and P=0.022, respectively). Both DRG-PRF and TFESI significantly improved NRS-11 and ODI scores (P<0.001), with no between-group difference. In the DRG-PRF group, CSP duration significantly increased on Day 1 and Week 1 (P=0.001 and P=0.004, respectively), whereas no significant change occurred in the TFESI group. DISCUSSION: These results suggest that shortened CSP duration reflects impaired spinal inhibition in LRP. While both DRG-PRF and TFESI were equally effective in reducing pain and disability, only DRG-PRF modified CSP parameters, indicating a potential central neuromodulatory effect. CSP evaluation may serve as an objective biomarker to clarify the mechanisms underlying interventional pain treatments.